2024
DOI: 10.3390/ijms25031582
|View full text |Cite
|
Sign up to set email alerts
|

PRAME Updated: Diagnostic, Prognostic, and Therapeutic Role in Skin Cancer

Fortunato Cassalia,
Andrea Danese,
Ina Tudurachi
et al.

Abstract: Preferentially Expressed Antigen in Melanoma (PRAME), a member of the cancer/testis antigen family, is central to the field of skin cancer diagnostics and therapeutics. As a nuclear receptor and transcriptional regulator, PRAME plays a critical role in inhibiting retinoic acid signalling, which is essential for cell differentiation and proliferation. Its aberrant overexpression in various malignancies, particularly cutaneous melanoma, is associated with more aggressive tumour phenotypes, positioning PRAME as b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Clinicians should be alert to lesions that do not resolve, such as warts and ulcers, as these should prompt consideration of more serious conditions. Immunohistochemistry and the use of markers such as PRAME can be very helpful in distinguishing melanoma from other malignancies such as clear cell sarcoma [41,44]. However, despite the interesting results, the conclusions of this review must be tempered by the limitations discussed above.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Clinicians should be alert to lesions that do not resolve, such as warts and ulcers, as these should prompt consideration of more serious conditions. Immunohistochemistry and the use of markers such as PRAME can be very helpful in distinguishing melanoma from other malignancies such as clear cell sarcoma [41,44]. However, despite the interesting results, the conclusions of this review must be tempered by the limitations discussed above.…”
Section: Discussionmentioning
confidence: 92%
“…The differentiation of AAM from sarcomas requires careful clinical evaluation, supported by histological and immunohistochemical analysis [40,42]. In this case, the use of PRAME as an immunohistochemical marker could be a valuable diagnostic aid; indeed, PRAME, which is expressed in melanoma but not in most sarcomas, could be an important discriminatory tool, improving the diagnostic accuracy of AAM [40][41][42][43][44]. Alternatively, traditional genetic studies may be very useful in the differential diagnosis between these two neoplasms [40,42].…”
Section: Discussionmentioning
confidence: 99%
“…The AUC values for the prediction of 1-year, 3-year and 5-year OS were 0.67, 0.71 and 0.70, respectively, indicating high reliability and accuracy.In addition, the high risk group had signi cantly lower OS than the low risk group. The three genes we screened to construct the model were MUC6, PRAME and VGF.Recent studies have shown that MUC6 expression is a preferred prognostic marker for invasive mucous adenocarcinoma of the lung [26].Preferentially Expressed Antigen in Melanoma (PRAME), a member of the cancer/testis antigen family, is central to the eld of skin cancer diagnostics and therapeutics [27].VGF:A prospective biomarker and therapeutic target for neuroendocrine and nervous system disorders [28].Studies on GARGs laid the foundation for PCa immunotherapy. PCa expresses a variety of tumor-speci c antigens recognized by T cells, and the growth rate of PCa cells is relatively slow.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor promoting activity of PRAME was discovered via its depletion in xenograft mouse tumor models ( 9 - 11 ). Therefore, targeting PRAME, either by exploiting its immunogenic or oncogenic potential, has been proposed as a strategy for tumor therapy ( 12 , 13 ). PRAME expression is upregulated by promoter DNA hypomethylation ( 14 , 15 ) and is stimulated by cooperation with myeloid zinc finger 1 ( 16 ).…”
Section: Introductionmentioning
confidence: 99%